Automotive braking system simulations V diagram approach - V. Gowda, Dankan; A C, Ramachandra; M N, Thippeswamy; C, Pandurangappa; Naidu P, Ramesh (International Journal of Engineering and Technology, 2018)
This Paper focus, on the different stages associated with the advancement of Automobile Braking Control system. Different V-Models (SIL, MIL, HIL, and DIL) are contrasted with the proposed V model for Hydraulic antilock braking system. The main objective of this research is to enable various loop simulations used in a variety of automotive industries, in order to analyze the performance of different safety functions. A vehicle model is used to represent a real vehicle in a model-based environment. Vehicle model is a sophisticated component, which makes use of two wheeler dynamics concepts to achieve a real vehicle behavior. In this research, an attempt is made to elaborate the various automotive simulations used starting from model in loop simulation to Driver in loop Simulation approaches followed by a V-diagram approach to develop the product. Here an ABS controller is taken as an example model for simulation.Â